2013
DOI: 10.1111/joa.12022
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating viable cell density in the intervertebral disc: blood supply in relation to disc height

Abstract: The intervertebral disc is an avascular tissue, maintained by a small population of cells that obtain nutrients mainly by diffusion from capillaries at the disc-vertebral body interface. Loss of this nutrient supply is thought to lead to disc degeneration, but how nutrient supply influences viable cell density is unclear. We investigated two factors that influence nutrient delivery to disc cells and hence cell viability: disc height and blood supply. We used bovine caudal discs as our model as these show a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 37 publications
4
38
0
1
Order By: Relevance
“…This appears to be inconsistent with the finding that diabetes decreased GAG content, yet obesity alone had no appreciable effect. However, Boubriak et al reported that endplate capillary size and density is increased with disc size [14]. In the current study, obese and diabetic rats had 34% greater disc cross-sectional areas, which could explain their greater RBC density.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This appears to be inconsistent with the finding that diabetes decreased GAG content, yet obesity alone had no appreciable effect. However, Boubriak et al reported that endplate capillary size and density is increased with disc size [14]. In the current study, obese and diabetic rats had 34% greater disc cross-sectional areas, which could explain their greater RBC density.…”
Section: Discussionsupporting
confidence: 45%
“…During the pre-diabetic state, increased insulin levels resulting from insulin resistance can have an anabolic effect on bone metabolism [11]. Any increase in bone formation in the endplate (sclerosis) could negatively impact disc health since the disc is avascular and thus, sclerosis could hinder the transport of nutrients and metabolites across the endplates to and from the disc [12][13][14]. Hyperglycemia may also be important.…”
Section: Introductionmentioning
confidence: 99%
“…Torsion angle of failure of coccygeal discs for rat and cattle was found to be very high at ~30° [97,98] in contrast to the human lumbar disc where the failure range is smaller ~10° [52]. Biochemical composition, cell density and the cell population lacking notochordal cells of the bovine tail IVD are highly similar to human lumbar IVD [99,100]. …”
Section: Animal Models For Organ Culturementioning
confidence: 99%
“…The uptake of lactic acid waste from the tissue can also be hindered, leading to a buildup within the intervertebral disc and a subsequent decrease in the pH to detrimental levels. Previous studies have shown that a reduced vertebral blood flow is associated with the presence of disc degeneration 36 and that viable cell density in the disc is related to the density of blood vessels in the adjacent vertebral bodies 37 .…”
Section: Change In Nutritional Supply and Vasculature Due To Cigarettmentioning
confidence: 99%